PERANCANGAN MADRASAH ALIYAH RAUDHATUL AMININ DI KECAMATAN SAMPANAHAN KABUPATEN KOTABARU - Herliani, Lilik; Oktaviana, Anna (UNIVERSITAS LAMBUNG MANGKURAT, 2023)
Education is one of the basic needs for humans. As the population increases, the need for education will also continue to increase. Madrasah Aliyah is one of the secondary education levels in formal education in Indonesia which is equivalent to Senior High School managed by the Ministry of Religious Affairs. The equalization and quality of Islamic education services is very important to do, especially in remote areas that may not have it at all, one of which is the Sampanahan District area of Kotabaru Regency. The problem raised from the design of this Madrasah Aliyah is how the concept of designing Madrasah Aliyah can optimize its function as an Islamic Education building. Architectural Programming method is used to optimize the function of Islamic education. The design concept applied to support the Islamic Education area is the concept of Islamic Architecture. The application on the design is with the division and arrangement of building masses in the area which is sorted according to the function and the culprit.